A Brief Review of the Latest Advancements of Massive Solar Thermal Collectors - Aquilanti, Alessia (2023)
Technologies that can contribute to the reduction of greenhouse gases are mandatory, and those based on solar energy are good candidates to achieve this. In this sense, massive solar thermal collectors are suitable technologies for supplying the primary energy demand of buildings. To design these devices, it is necessary to fully understand the physics of the problem before proposing any new optimized solution. This review aims to briefly summarize significant aspects regarding the current state of development of these solar technologies. Attention is paid to works devoted to experimental studies to analyze the behavior of these systems, as well as numerical models to predict the physics of the problem. Furthermore, the future directions and prospects in the field of massive collectors are briefly described. The main novelty of this review is to provide a comprehensive overview that summarizes the works done so far in the field over the past 30 years, which allows the reader to delve deeper into the topic. According to the reviewed works, it can be concluded that these technologies can contribute to the reduction of greenhouse gases while at the same time being excellent examples of the integration of solar energy devices with buildings.